Collection Development in Selected College Libraries of Golaghat District: a Survey - Junaki Borthakur (AG Volumes, 2023)
College libraries are considered as centres of learning that aim to satisfy user information requirements and this can be possible only through proper collection. Collection development is a very important function of college library. It is a backbone of a library system. It is a systematic process of building library collection to fulfill users’ information needs. Collection development process includes acquisition, selection, evaluation and preservation of resources according to users’ information requirement. This study highlights the collection development of selected college libraries of Golaghat District. This study helps to explore the collection of printed materials such as text book, reference book, newspapers etc. and non-printed materials such as e book e Journals etc. of selected college libraries. This study also helps to know about the automation status of the selected libraries. This study found that some of the college libraries of Golaghat District have a good collection of printed and non-printed materials and some of them are very poor in collection. Every surveyed library should focus on library automation status and must try to improve it.